MODERN COATING TECHNOLOGIES - KUCHERENKO, Yuliya (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The development of the country is determined by the efficiency of enterprises and organizations, which should simply survive in difficult conditions, and pursue an active strategy of transformation. Innovations in the technology of protective and decorative metal coatings create the necessary level of competition in the domestic paint and varnish coating.Innovative development of the country's economy is one of the highest priorities of state policy. The strategy of modernization is determined by the consistent transition of the economy to an innovative model of development to solve the problem of strategic support for sustainable and long-term dynamics of innovation processes. However, today there is no necessary level of competition in the domestic innovation market and entrepreneurs are aware of the importance of innovation in creating competitive advantages, as well as an adequate legal framework governing relations in the field of innovation. In addition, the generation of knowledge takes place in the public sphere, the application of this knowledge or the implementation of the obtained scientific and technical results is in the commercial industry. Metal has been and remains the main structural material of the industry - from means of production to consumer products, and the primary consumer properties of the product include its appearance and durability. Rust can kill these qualities in a matter of months and days, so perhaps more important is the quality of the product itself, and the quality of its coating.In this paper, an analysis of modern coating technologies is carried out, the strengths and weaknesses of different coating technologies are identified.
Keywords: coating technologies; corrosion protection; metal; non-metal (ceramic); polymer coatings; electrochemical technologies